Study on Solubilization and Stabilization of Eight Flavonoids by 17 Chinese Herbal Polysaccharides - Xuexiao Cao; Lei Wang; Meiqi Liu; Xiaoliang Ren; Tingting Han; Yanru Deng (Journal of Chemistry)
Flavonoids are important active components of traditional Chinese medicines (TCMs) because of their many biological activities. We studied the interaction between 17 polysaccharides and eight flavonoids via high-performance liquid chromatography (HPLC) and the effect of the interactions on the solubility and stability of the flavonoids. The effect of the polysaccharides on the solubility of flavonoids was analyzed by statistical methods and showed significant solubility improvements. The constant temperature acceleration method (90°C/pH 9 buffer solution) was used to measure the degradation kinetics and half-life of flavonoids with and without polysaccharides. All the polysaccharides displayed a stabilizing effect on all eight flavonoids. The stabilizing effects varied in the order: quercetin, baicalein > baicalin > galuteolin > daidzin > rutin > luteolin > daidzien. The phase-solubility method was applied to quercetin and baicalein to study the mechanism of action of the polysaccharides. It appeared that the two flavonoids could form 1 : 1 inclusion complexes with polysaccharides, which may be one of the factors increasing solubility and stability. These findings increase our understanding of the role of endogenous polysaccharides in TCM in improving the stability and bioavailability of bioactive flavonoids.